Propagation of Sukun (Artocarpus altilis (Parkinson) Fosberg) Through In Vitro Shoot Proliferation - Imelda, Maria; Wulansari, Aida; Sari, Laela (Annales Bogorienses, 2009)
Sukun (Artocarpus altilis (Parkinson) Fosberg) of the Moraceaae is a big tree which can grow to 15-20 m in height and native to the Asia-Pasific region. Beside its delicious fruit, sukun is also known as a traditional herbal medicinal plant in the region, including Indonesia. Nearly all parts of the plant, such as roots, stems and leaves are believed by local communities to be capable of curing liver disease, hypertension, cardiac arrest, toothache, renal problem and even skin itchiness. The collaborative research between LIPI and PR China, on developing herbal medicines indicated that sukun has a great potential for treating cardiovascular disease. However, the availability of raw materials still poses a big constraint for the industry of herbal medicines. Generally, sukun is propagated by root or stem cuttings, since in Indonesia sukun does not produce any seeds. However such method only produces limited planting materials. In general tissue culture propagated plants have many advantages, namely being clonal, free from pest and diseases, more uniform, and allowing a high rate of plant multiplication. Therefore, the technique for sukun propagation has been developed by the LIPI Research Centre for Biotechnology. In this research the effects of 1-5 mg/l benzyl amino purine (BAP) and 20-40 mg/l adenine sulphate (AS)on shoot bud proliferation were investigated using lateral shoot buds on a modified Murashige and Skoog (MS) medium with addition of 150 ml/l coconut water (CW). Shoots were rooted on MS medium without plant growth regulators (PGRs). The results showed that the best medium for in vitro shoot proliferation was a modified MS medium containing 2 mg/l BAP, 40 mg/l AS and 150 ml/l CW. The best medium for rooting is MS medium containing 1 mg indole butyric acid (IBA), producing roots within 3 weeks.